Acquired Drug Resistance Enhances Imidazoquinoline Efflux by P-Glycoprotein - Anunay J. Pulukuri; Anthony J. Burt; Larissa K. Opp; Colin M. McDowell; Maryam Davaritouchaee; Amy E. Nielsen; Rock J. Mancini (MDPI AG, 2021)
Multidrug-Resistant (MDR) cancers attenuate chemotherapeutic efficacy through drug efflux, a process that transports drugs from within a cell to the extracellular space via ABC (ATP-Binding Cassette) transporters, including P-glycoprotein 1 (P-gp or ABCB1/MDR1). Conversely, Toll-Like Receptor (TLR) agonist immunotherapies modulate activity of tumor-infiltrating immune cells in local proximity to cancer cells and could, therefore, benefit from the enhanced drug efflux in MDR cancers. However, the effect of acquired drug resistance on TLR agonist efflux is largely unknown. We begin to address this by investigating P-gp mediated efflux of TLR 7/8 agonists. First, we used functionalized liposomes to determine that imidazoquinoline TLR agonists Imiquimod, Resiquimod, and Gardiquimod are substrates for P-gp. Interestingly, the least potent imidazoquinoline (Imiquimod) was the best P-gp substrate. Next, we compared imidazoquinoline efflux in MDR cancer cell lines with enhanced P-gp expression relative to parent cancer cell lines. Using P-gp competitive substrates and inhibitors, we observed that imidazoquinoline efflux occurs through P-gp and, for Imiquimod, is enhanced as a consequence of acquired drug resistance. This suggests that enhancing efflux susceptibility could be an important consideration in the rational design of next generation immunotherapies that modulate activity of tumor-infiltrating immune cells.